Sucesso reprodutivo de Salminus brasiliensis (Cuvier, 1816) : variações intra e interanual e a influência de variações ambientais. - Rosa, Rafael Rogério (2016)
The reproduction of freshwater fish occurs annually in environments that provide favorable environmental conditions for spawning and subsequent survival and growth of their larvae. The aim of this study was to evaluate the spatial and temporal distribution of larvae Salminus brasiliensis in order to understand the intra and interannual variations in their abundance and the influence of environmental variables on reproduction. Samples were collected at different biotypes (river, backwater and lagoon) of Ivinheima River floodplain of the upper Paraná River, Brazil. At the same time, were obtained temperature, dissolved oxygen, pH, electrical conductivity, river level and rainfall. The larvae of S. brasiliensis were captured mainly in the months of October and January, the biotope river and backwater and no significant difference in relation to its vertical and nycterohemeral. It is estimated that this species can migrate over 200 km to reproduce in the river Ivinheima and its tributaries as the river Guiraí. The temperature, the river level, pH and dissolved oxygen were the main variables that influence the larvae density. The importance of maintaining this last damming free lotic and is essential for the maintenance of natural stocks, especially of S. brasiliensis, because mechanisms such as intensity of flooding and delay flooding are factors that act directly on the reproductive success of the species and depend on these natural conditions. Salminus brasiliensis is a key species to propose management and conservation measures for all fish population, once guaranteed the reproductive success of this species, other migratory and sedentary species will also benefit.